2021
DOI: 10.1111/ajt.16075
|View full text |Cite
|
Sign up to set email alerts
|

Extinguishing burnout: National analysis of predictors and effects of burnout in abdominal transplant surgery fellows

Abstract: Burnout among surgeons has been attributed to increased workload and decreased autonomy. Although prior studies have examined burnout among transplant surgeons, no studies have evaluated burnout in abdominal transplant surgery fellows. The objective of our study was to identify predictors of burnout and understand its impact on personal and patient care during fellowship. A survey was sent to all abdominal transplant surgery fellows in an American Society of Transplant Surgeons–accredited fellowship. The respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Post‐traumatic stress is not unique to solid organ transplant clinicians and has been identified in other pediatric clinicians 22,23 . Our study found that 15% of clinicians reported post‐traumatic stress symptoms.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Post‐traumatic stress is not unique to solid organ transplant clinicians and has been identified in other pediatric clinicians 22,23 . Our study found that 15% of clinicians reported post‐traumatic stress symptoms.…”
Section: Discussionmentioning
confidence: 53%
“…Our study found that 15% of clinicians reported post‐traumatic stress symptoms. This is in the range of rates reported in studies of other pediatric subspecialties (ie, 2% in general pediatricians 23 to 20% in pediatric intensive care clinicians) 22 . Early career intensive care faculty and nurses have been found to be more likely to report burnout and post‐traumatic stress symptoms than more senior clinicians 24 .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…This will increase the stress of making organ utilization decisions. Transplant surgery is becoming a less popular career choice, and surgeon burnout due to overwork and anti‐social hours is a pressing concern in many countries [63–65].…”
Section: Reasons Why Organs Are Declinedmentioning
confidence: 99%